"Audience exchange": cultivating peer-to-peer dialogue at unfamiliar arts events. (2nd May 2017) - Pitts, Stephanie; Gross, Jonathan
Abstract : Purpose: The purpose of this paper is to demonstrate the usefulness of the "audience exchange" approach for audience development and research, and to highlight the insights offered by peer-to-peer dialogue in understanding experiences of unfamiliar arts. Design/methodology/approach: Using a case study with contemporary arts audiences, and setting this in the wider context of studies with other first-time attenders at a range of arts events, the paper explores the use of the "audience exchange" method, in which facilitated conversations after performance events allow newcomers to reflect upon and deepen their first-time encounters with live arts. Findings: The study demonstrates the way in which conversations about arts events can enrich audience experience, and shows how participants use exploratory and emotional language to articulate their understanding of unfamiliar arts events. Peer-to-peer learning occurs through these conversations, in ways that could be further supported by arts organisations as a valuable tool for audience development. The audience exchange discussions also reveal the varieties of participation from "drifting" to full attention that are all part of audience engagement. Research limitations/implications: This is a small-scale, qualitative study, and the method has potential to be tested in future studies with a greater variety of participants (e.g. younger or more ethnically diverse groups). Practical implications: Use of the audience exchange for enriching experiences of first-time attendance could be adopted by arts organisations as a regular part of their audience engagement. Greater understanding of how new audience members draw on prior cultural experiences in finding the language to articulate their first impressions of an unfamiliar arts event could be valuable for targeted marketing and increasing accessibility. Originality/value: The originality of this study lies in its elaboration of the audience exchange method, and its focus on the language and peer-to-peer learning evident in the facilitated post-performance discussions.